THE EFFECT OF PREGNANCY MILK ON THE EXPRESSION OF KALLIKREIN RELATED PEPTIDASE-4 (KLK-4) AND COLLAGEN TYPE 1 (Coll-1) IN AMELOGENESIS - Sandy Christiono; Welly Anggarani (Dentino : Jurnal Kedokteran Gigi, 2021)
Background: Tooth development during embryonic period is a complex process and requires adequate nutrients for the formation of healthy dental tissues. Kallikrein-related peptidase-4 (KLK-4) and collagen type 1 (Coll-1) are serine proteinases secreted by ameloblast during the transition and maturation stages of the amelogenesis processes, functioning to degrade the protein matrixes, so that the enamel can reach its final hardness. Pregnancy milk contains various nutrients expected to increase the KLK-4 expression of ameloblast cells in tooth development processes Purpose: This study aimed at determining the influence of pregnancy milk on the KLK-4 and collagen type 1 (Coll-1) expression of ameloblast cells in the tooth development processes.study Method The research subjects comprised of 10 pregnant female mice (Mus Musculus L.) that were divided into: control group (given sterile aquadest) and treatment group (given pregnancy milk + sterile aquadest) for 18 days followed by the  collection of the tooth germ. The specimens were then stained using Imunnohistochemistry to see the KLK-4 and Coll-1 expressions. The data were analyzed using a pathway analysis. Result: The average KLK-4 and Coll-1 expression in the treatment group were higher than those in the control group. Based the pathway analysis, there were direct correlation of Pregnancy milk with Coll-1 expression and that with KLK-4 and Coll-1 expression as well as indirect correlation of pregnancy milk with KLK-4 expression. Conclusion: Pregnancy milk influences the Kallikrein-related peptidase-4 (KLK-4) and Coll-1 expression of ameloblast cells in the tooth development of the mice’s fetusesKeywords: Coll-1 pregnancy milk, Kallikrein-related peptidase-4 (KLK-4), Tooth development